Treatment of Low Milk Supply. Issue 6 (November 2022) - Spatz, Diane L.
Abstract : The formula shortage several months ago highlighted the experiences of many women with breastfeeding challenges. Our breastfeeding expert, Dr. Spatz, provides an overview of the state of treatment for low breast milk supply in the United States.